KORELASI ANTARA MINAT DENGAN PRESTASI BELAJAR PADA PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN SISWA KELAS X MIPA 2 SEKOLAH MENENGAH ATAS NEGERI 1 SEPAUK TAHUN PELAJARAN 2021/2022 - Hartini, Agnesia; Mardawani, Mardawani; Tinum, Tinum (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2022)
The purpose of this study wa to determine the correlation between interest and learning achievement in Pancasila education learning and citizenship for students of class X MIPA 2 State Senior High School 1 Sepauk in the 2021/2022 academic year. This research uses quantitative methods with the form of interactiberelationship study research. The sample in this study were students of class X MIPA 2  State Senior High School 1 Sepauk totaling 30 students. Tehciques and data collection tools using questionnaires and documentation. Hypothesis testing includes normality test,simple regression analysis, correlation analysis, and t test. The research data wa obtained from the resukts of a questionnaire on learning interest and student achievement from the academic report cards for the odd semester 2021/2022. Based on the calcution of the product moment correlation test, it is known that the correlation value is 0,776 that the interval coefficient is 0,60-0,779 and level og the relationship is relatively strong. Based on te t-test it is known that tcount is 0,851 and t-table = n-2 =30-2 is 28 t-table =0,374, so 0,851 > 0,374  Ha is accepted. So it can be said that there is a significant correlation between interest and learning achievement in Pancasila education learning and citizenship for students of class X MIPA 2 State Senior High School 1 Sepauk in the 2021/2022 academic year. Keywords: Interest, and Student Achievement